Microradiography of Microcalcifications in Breast Specimen: A New Histological Correlation Procedure and the Effect of Improved Resolution on Diagnostic Validity. (11th October 2012) - Langen, H.-J.; Koehler, S.; Bielmeier, J.; Jocher, R.; Kranzfelder, D.; Jagusch, N.; Treutlein, G.; Wetzler, Th.; Müller, J.; Ott, G.
Abstract : Introduction . Does high-resolution visualization of microcalcifications improve diagnostic reliability? Method . X-rays were taken of mamma specimens with microcalcifications in 32 patients (10 malignant; 22 benign) using conventional radiography (12 Lp/mm) and high-resolution radiography (2000 Lp/mm). Histological sections were subsequently prepared and correlated to the microradiographic image and every calcification was assigned an exact malignant or benign histological diagnosis. Five radiologists classified single groups of calcifications in both methods according to the BIRADS classification system. Results . Using microradiography microcalcifications can be shown in high resolution at the cell level including histological correlation. In some cases, the diagnostic validity was improved by the high resolution in microradiography. In other cases, the high resolution resulted in more visible calcifications, thus giving benign calcifications a malignant appearance. In the BIRADS 2 and 3 group, the probability of malignancy was 28.6% in the conventional radiography evaluation and 37.8% in the microradiography evaluation. In the BIRADS 4 and 5 group, the probability of malignancy was 34.2% in the conventional radiography evaluation and 24.4% in the microradiography evaluation. The differences were not significant. Summary . Overall, the improved resolution in microradiography did not show an improvement in diagnostic accuracy compared to conventional radiography.